Analisis Tingkat Kesehatan Bank Syariah Indonesia Menggunakan Metode RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) Periode 2021-2024 - Susanto, Eko; Muhammad Rizqi Azizi (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to determine how the health level of Bank Syariah Indonesia uses the RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) method for the 2021-2024 period. This research is quantitative with descriptive type. The results show that the overall condition of the bank is in a very good condition and has the ability to deal with the negative impact of changes in business conditions and other external factors.